ChemInform Abstract: Gold‐Catalyzed Functionalization of Unactivated C(sp3)—H Bonds by Hydride Transfer Facilitated by Alkynylspirocyclopropanes. Issue 12 (14th March 2013) - Barluenga, Jose; Sigueiro, Rita; Vicente, Ruben; Ballesteros, Alfredo; Tomas, Miguel; Rodriguez, Miguel A.
Abstract The 1, 5‐hydride transfer of alkynylcyclopropanes bearing a spiran core is investigated under different conditions: pentalene derivatives or bicyclic systems are formed.